Broad-Scale Phosphoprotein Profiling of Beta Adrenergic Receptor (β-AR) Signaling Reveals Novel Phosphorylation and Dephosphorylation Events - Chruscinski, Andrzej J.; Singh, Harvir; Chan, Steven M.; Utz, Paul J. (PLOS ONE, 2013)
β-adrenergic receptors (β-ARs) are model G-protein coupled receptors that mediate signal transduction in the sympathetic nervous system. Despite the widespread clinical use of agents that target β-ARs, the signaling pathways that operate downstream of β-AR stimulation have not yet been completely elucidated. Here, we utilized a lysate microarray approach to obtain a broad-scale perspective of phosphoprotein signaling downstream of β-AR. We monitored the time course of phosphorylation states of 54 proteins after β-AR activation mouse embryonic fibroblast (MEF) cells. In response to stimulation with the non-selective β-AR agonist isoproterenol, we observed previously described phosphorylation events such as ERK1/2(T202/Y204) and CREB(S133), but also novel phosphorylation events such as Cdc2(Y15) and Pyk2(Y402). All of these events were mediated through cAMP and PKA as they were reproduced by stimulation with the adenylyl cyclase activator forskolin and were blocked by treatment with H89, a PKA inhibitor. In addition, we also observed a number of novel isoproterenol-induced protein dephosphorylation events in target substrates of the PI3K/AKT pathway: GSK3β(S9), 4E-BP1(S65), and p70s6k(T389). These dephosphorylations were dependent on cAMP, but were independent of PKA and correlated with reduced PI3K/AKT activity. Isoproterenol stimulation also led to a cAMP-dependent dephosphorylation of PP1α(T320), a modification known to correlate with enhanced activity of this phosphatase. Dephosphorylation of PP1α coincided with the secondary decline in phosphorylation of some PKA-phosphorylated substrates, suggesting that PP1α may act in a feedback loop to return these phosphorylations to baseline. In summary, lysate microarrays are a powerful tool to profile phosphoprotein signaling and have provided a broad-scale perspective of how β-AR signaling can regulate key pathways involved in cell growth and metabolism.